Addressing self-criticism in depression using CBT-based emotion-focused chairwork: study protocol of a randomised controlled trial - Julia Kroener; Zrinka Sosic-Vasic; Jacqueline Mahler (BMJ Open, 2023)
Introduction Self-criticism is a key feature in people diagnosed with depression, resulting in significant psychological distress. Despite the fact that cognitive–behavioural treatments are readily available, a significant number of patients report experiencing cognitive, but not emotional, change following therapy, resulting in the maintenance of psychological symptoms. Additionally, interventions targeting emotional experiencing, such as chairwork, are generally implemented within large-scale therapeutic treatments. Therefore, within the present study, we aim to evaluate the efficacy and safety of a short intervention using emotion-focused chairwork to target self-criticism in patients diagnosed with depression.Methods and analysis The study is designed as a randomised controlled trial with two parallel arms. 62 patients diagnosed with depression will be randomised to the intervention group or the waiting-list control group receiving treatment as usual. The intervention comprises of three treatment sessions using the chairwork technique over the course of 3 weeks. Outcome assessments will take place 1 week before the first treatment session, as well as 1 week and 3 months after the last treatment session. The primary outcomes are self-criticism and self-compassion. Secondary outcomes assess depressive symptoms, emotion regulation and overall self-esteem. Statistical analysis will be performed using intention-to-treat analysis, as well as per-protocol analysis implementing linear-mixed models.Ethics and dissemination The study was approved by the Ethics Committee of the State Chamber of Physicians in Baden-Wuerttemberg, Germany (approval number: F-2023-12). Scientific findings shall be published in peer-reviewed journals to inform prospective clinical studies focusing on the implementation of chairwork within clinical practice.Trial registration number German Clinical Trials Register (DRKS00031307; https://drks.de/search/de/trial/DRKS00031307).